Sex and salvation imagining the future in Madagascar - Cole, Jennifer, 1966- (University of Chicago Press, 2010)
As much of the intense political and social changes in Madagascar revolve around urban youth, who view themselves as avatars of modernity, this book argues that traditional social science offers inadequate theorizations of generational change and its contribution to broader cultural historical processes.